IMPLEMENTASI ARAH DASAR KAS 2016-2020 MEMBANGUN GEREJA KAS YANG INKLUSIF, INOVATIF DAN TRANSFORMATIF DEMI TERWUJUDNYA PERADABAN KASIH DI INDONESIA - Sugiyana Sugiyana (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2021)
The People of God of the Archdiocese of Semarang (KAS) as a community of believers under the guidance of the Holy Spirit are determined and work together to fight for the realization of a civilization of love in Indonesia. The civilization of love is characterized by a shared life based on a mindset, attitude pattern and behavior pattern that is directed towards a prosperous, dignified and faithful life. To realize these ideals, all parties are involved through improving life intelligent, tough, missionary and dialogical believers; personal development, family, environment and groups to play a role in society fighting for fair public policies, prioritizing the weak, small, marginalized and disabled, democratic, involving everyone to build society without being divided by religion, class, ethnicity, group and personal interests; improve charitable and empowerment services for the realization of welfare, especially basic needs; encourage lay people and activists to get involved in social, cultural, economic, political, environmental conservation movements that have a positive impact on society; assisting young cadres to become agents of change in the Church and Society.These efforts are based on an inclusive, innovative and transformative spirit. It is impossible for the church to work alone to create a civilization of love. Therefore, it must cooperate with all members of the community, always looking for ways and forms to increase the power of change in every action. The Semarang Archdiocese's Pastoral Work Council, through its commissions, endeavors to compile, implement, evaluate its work program so that it is directed at the realization of a civilization of love by involving community activists at the vicars and parish levels. It is hoped that this joint movement will result in significant progress in the Semarang Archdiocese Church becoming an inclusive, innovative and transformative Church for the civilization of love in Indonesian society. The church becomes Lumen Gentium (light of the nation) in the movement to realize prosperity, dignity and faith.